Tomografía Computarizada en Bajas Latitudes de la Ionósfera: Avances Recientes - Medrano, Melissa (2018)
The electron density distribution is, arguably, the most relevant physical parameter to study the geospace electrodynamics. There are several high precision remote sensing techniques to estimate this distribution, unfortunately, most of them are constrained to a one-dimensional reconstruction. In contrast, Ionospheric tomography is probably the most promising alternative to produce 2D or 3D profiles. It uses satellites signals, that travel along a defined reconstruction plane, to construct a linear model based on the theoretical relation between this signals phases and the electron density of ionospheric plasma. The solution of this system provides an estimation of the electron density distribution. The use this technique aims to reconstruct density profiles, both, for stable states of the ionosphere and states in which the ionosphere contains plasma irregularities.